Preserve a Voucher Specimen! The Critical Need for Integrating Natural History Collections in Infectious Disease Studies - Thompson, Cody W.; Phelps, Kendra L.; Allard, Marc W.; Cook, Joseph A.; Dunnum, Jonathan L.; Ferguson, Adam W.; Gelang, Magnus; Khan, Faisal Ali Anwarali; Paul, Deborah L.; Reeder, DeeAnn M.; Simmons, Nancy B.; Vanhove, Maarten P. M.; et al. (mBio, 2021)
Despite being nearly 10 months into the COVID-19 (coronavirus disease 2019) pandemic, the definitive animal host for SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), the causal agent of COVID-19, remains unknown. Unfortunately, similar problems exist for other betacoronaviruses, and no vouchered specimens exist to corroborate host species identification for most of these pathogens. Despite being nearly 10 months into the COVID-19 (coronavirus disease 2019) pandemic, the definitive animal host for SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), the causal agent of COVID-19, remains unknown. Unfortunately, similar problems exist for other betacoronaviruses, and no vouchered specimens exist to corroborate host species identification for most of these pathogens. This most basic information is critical to the full understanding and mitigation of emerging zoonotic diseases. To overcome this hurdle, we recommend that host-pathogen researchers adopt vouchering practices and collaborate with natural history collections to permanently archive microbiological samples and host specimens. Vouchered specimens and associated samples provide both repeatability and extension to host-pathogen studies, and using them mobilizes a large workforce (i.e., biodiversity scientists) to assist in pandemic preparedness. We review several well-known examples that successfully integrate host-pathogen research with natural history collections (e.g., yellow fever, hantaviruses, helminths). However, vouchering remains an underutilized practice in such studies. Using an online survey, we assessed vouchering practices used by microbiologists (e.g., bacteriologists, parasitologists, virologists) in host-pathogen research. A much greater number of respondents permanently archive microbiological samples than archive host specimens, and less than half of respondents voucher host specimens from which microbiological samples were lethally collected. To foster collaborations between microbiologists and natural history collections, we provide recommendations for integrating vouchering techniques and archiving of microbiological samples into host-pathogen studies. This integrative approach exemplifies the premise underlying One Health initiatives, providing critical infrastructure for addressing related issues ranging from public health to global climate change and the biodiversity crisis.